Wellbeing of the Society: A Maqasid al-Shari’ah Approach - Abdul Rasool, Mohamed Saladin; Mohd Yusof, Mohamed Azmil; Ali, Siti Mariam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Wellbeing is generally seen as an example of the condition of households, society, and people. The issue of wellbeing in the modernized world has been reviewed and explained in various ways as it is a crucial issue for a household that acts as a reflection of the comfort status among humanity. From the Islamic perspective, wellbeing can be widely explained through inner and outer fulfilment, and guiding people through a peaceful life, named as hayat al-tayyibah. The ultimate objective of the paper is to present a framework of wellbeing from the Maqasid al-Shari’âh principles. Each dimension of the principles were deliberated according to the views of scholars from the perspective of the Shari’ah. The paper highlights the operation of Maqasid al-Shari’ah as a measurable multidimensional concept, a relatively new discipline in various fields of social sciences and economics. Studies have shown that wellbeing could be explained in a multidimensional perspective using these principles.